Pengaruh Model Reading Concept Connection Discussion Evaluation (RCCDE) terhadap Berpikir Kritis - Arifatus Soleha; Siti Roudlotul Hikamah; Imam Bukhori Muslim (Pendidikan Biologi,Universitas Islam Jember, 2019)
The effect of model the Reading Concept Connection Discussion Evaluation (RCCDE) on critical thinking on water pollution material aims to determine the increase in critical thinking. Kind of research is a quasi experiment. Researchers in take samples using a purposive sampling technique with respondents in two classes. Data analysis using Anova. The total same of students is 22 in the experimental class using RCCDE and the control class using conventional methods. Based on the results of the analysis, it's can be concluded that there is an influence of the RCCDE model, on increasing critical thinking on Water Pollution material. Can be seen from the ANOVA test results obtained sig. 0,000 <0.05 (<0.050). Then, Ha is accepted. Based on these results, it be concluded that the use of the RCCDE model can improve critical thinking.